The Effectiveness of using Short Story on Students’ reading Comprehension - Zumrotun Lutfia; Dodi Widia Nanda; Dina Fitria (Universitas Pahlawan Tuanku Tambusai, 2023)
The aimed of this research was to determine tu effect of using short story on students’ reading comprehension at MAS Raudlatul Asror Tebo. There were some problems in this research. First, they they did not have comprehending in reading and were unable to understand the content of the text. Second, they had difficulty getting information from the English text. Last, they still have inadequate vocabulary. The purpose of this research was to determine the effectiveness of using short story in teaching reading. The population of this research were 14 students. The sampling technique in this research used total sampling. The sample of this research X IPS consists of 14 students. The method used in this study is a quantitative method using pre-experimental design, one group pretest-posttest The data collection technique was taken by giving pre-test and post-test in the form of a multiple choice of 25 questions. Data analysis technique to improve reading comprehension used normality test and paired sample t-test. The result of paired sample t-test showed that the significance level was 0.000<0.05, wich mean Ho is rejected and Ha is accepted. So, it concluded the Short Story was effective to improve students reading comprehension at MAS Radlatul Asror Tebo